Terror e imperialismo: el caso de Mitilene - Gil, Luis (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2007)
According to Thucydides, unlike others (those of Naxos, Thasos, Euboea, Samos, Amphipolis) the ajpovstasi" of Mytilene marks a turning point in the Peloponnesian war. This paper analyzes Cleon’s and Diodotus’ speeches (Thuc. III 37-48) in the light of contemporay ideas on freedom, crime and punishment (statements of Hdt, Thuc., Xen., Lys., Dem.), also taking into account the logos epitaphios and Pericles’ last speech. Cleon’s line of argument is based upon to; divkaion (viewed as retalation) and to; sumfevron on behalf of Athens. Diodotus argues exclusively on the basis of convenience. For the first time in Western history Diodotus contends that death penalty is no deterrent for crime and stands for sparing the Mytilenean demos in the execution of all men proposed by Cleon, since the demos is Athens’ only remaining ally in the Attic League of cities. The cause of increasing brutality in war is seemingly ascribed by Thucydides to the judicial oratory used in political deliberations (exemplified by Cleon), and to its progressive ideologization, the starting point of which can be seen in Diodotus’ speech. Cities must seek and conclude alliances not with governments in place, but with the faction in the other city that bears the greatest political affinity with them. Such ideologization transforms international conflicts between poleis into civil wars, usually more ruthless and sanguinary than external wars.